Pengaruh Loneliness terhadap Komitmen pada Anggota Satuan Brimob Polda Sumatera Barat yang Menjalani Pernikahan Jarak Jauh - Talsi, Nadhila Putri; Rinaldi, Rinaldi (Lembaga Yasin AlSys, 2024)
This study aims to identify the effect of loneliness on commitment in members of the West Sumatra Police Brimob Unit who undergo long-distance marriage. The research method used is quantitative with purposive sampling technique. The sample consisted of 60 Brimob members aged 18-25 years. Data collection used the UCLA Loneliness Scale and Commitment Measurement. Data analysis was performed with simple linear regression. The results showed a significant influence between loneliness and commitment of 26.7% (R=-0.517, R square=0.267, p<0.05). The subject's level of loneliness was tend to be very high category, while commitment was in the medium category tending to be low. Loneliness experienced includes social and emotional aspects. On the commitment scale, aspects of psychological attachment were in the very low category, while aspects of long-term orientation and desire to maintain the relationship were in the moderate category. It was concluded that the higher the level of loneliness, the lower the perceived commitment. This finding confirms the importance of addressing loneliness in the context of long-distance marriage to maintain marital commitment.